Ankle syndesmotic instability assessment using a three-dimensional distance mapping algorithm: a cadaveric pilot WBCT study - Dibbern, Kevin; Talaski, Grayson; Schmidt, Eli; Jasper, Ryan; Mallavarapu, Vineel; Jones, Matthew; Stebral, Hannah; Behrens, Andrew; Alencar Mendes de Carvalho, Kepler; Chun Kim, Ki; et al. (Journal of the Foot & Ankle, 2022)
Objective: This cadaveric pilot study was to develop a weight bearing computed tomography (WBCT) three-dimensional (3D) distance mapping algorithm that would allow for detection of syndesmotic instability. Methods: Pilot study, two cadaveric specimens. Syndesmotic instability was induced by release of all syndesmotic ligaments through a conventional lateral ankle approach. WBCT imaging under simulated weight bearing was acquired before and after syndesmotic destabilization. Syndesmotic incisura and ankle gutter distances were assessed using a 3D distance mapping WBCT algorithm. Results: We found increases in the overall mean syndesmotic distances in the injured syndesmosis when compared to pre-injury state, and color coded distance maps allowed easy interpretation of the syndesmotic widening following ligament sectioning and destabilization of the syndesmotic joint. Conclusion: The WBCT 3D distance mapping algorithm has the potential to allow detection of mild syndesmotic instability with a relatively ease of interpretation by using color-coded distance maps. Level of Evidence V; Cadaveric Study.